Visual astronomy : a guide to understanding the night sky - Photinos, Panos (IOP (Series). Release 1., 2015)
This book introduces the basics of observational astronomy. It explains the essentials of time and coordinate systems, and their use in basic observations of the night sky. The fundamental concepts and terminology are introduced in simple language making very little use of equations and math. Examples illustrate how to select the relevant information from widely accessible resources, and how to use the information to determine what is visible and when it is visible from the reader's particular location. Particular attention is paid to the dependence of the appearance and motion on the observer's location, by extending the discussion to include various latitudes in both North and South hemispheres.